Colonization of Fusarium oxysporum transformed with the red fluorescence protein gene (tdTomato) mediated by Agrobacterium tumefaciens in roots of two avocado cultivars (Research, Society and Development, 2021)
Avocado (Persea americana) is a fruit crop of economic importance in Ecuador. Currently, a low incidence of Phytophthora cinnamomi has been reported, however, there are other soil pathogens that can affect this crop, even at the initial stages of plant multiplication (nursery), for this reason the use of rootstocks that tolerate these biotic adversities is recommended. In this research, the fungus Fusarium oxysporum was isolated from roots of nursery seedlings with symptoms of necrosis. In addition, an isolate of this pathogenic fungus modified with a strain of Agrobacterium tumefaciens was used to determine the infection of F. oxysporum in the roots of the Fuerte (commercial) and Criollo (local) cultivars. The results allowed to infer that the cultivar Criollo presented a greater tolerance to F. oxysporum than the cultivar Fuerte, which corroborates its use as a rootstock for commercial avocado varieties. Furthermore, to our knowledge, this is the first report of F. oxysporum affecting avocado nursery seedlings in Ecuador.